Prediction the Number of Ship Passengers in Ports Tagulandang Using the Triple Exponential Smoothing (TES) Method - Morisa Martha Kasawehi; Djoni Hatidja; Yohanes Andreas Robert Langi (Sam Ratulangi University, 2023)
The purpose of this study is to predict the number of ship passengers at Tagulandang Port. The data in this study are secondary data taken from Class III Ulu Siau Harbor Master Office in the Tagulandang Working Area. In addition, the data used is the number of passengers departing from Tagulandang Port from January 2018 to December 2022. The analysis method used is the TES method which consists of two models, namely the additive model and the multiplicative model. After analysis, it is predicted that the number of departing passengers will increase in January and December 2023. Based on the prediction results, the most number of passengers will be in December 2023, which is 1354 people, which is predicted to increase the number of passengers from the previous year. Meanwhile, the prediction for the least number of passengers is in April 2023, namely 588 people, which is predicted to increase from the previous year. The best model based on the value of the accuracy of the forecasting model is the multiplicative model with a MAPE value of 11.601%. Keywords: Multiplicative model; Tagulandang port; triple exponential smoothing